Studi Deskriptif tentang Tingkat Pemahaman Konsep Keanekaragaman Hayati dan Implikasinya dalam Pembelajaran Biologi di SMA Negeri 1 Pineleng - Akulina Kelitubun; M. Herry Sumampouw; Nova L. I. M. Ogi (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
Conceptual understanding is an important aspect of learning biology because it reflects the extent to which students can internalize knowledge and relate it to real life. This study aims to analyse the level of understanding of the concept of biodiversity of students and identify supporting and inhibiting factors in the biology learning process. The research was conducted in class X of SMA Negeri 1 Pineleng with a descriptive qualitative approach. Data was collected through observation, written tests, questionnaires, teacher interviews, and documentation. Conceptual comprehension is measured using three main indicators: the ability to restate concepts, classify objects based on certain properties, and provide examples rather than definitions. The results showed that 87.5% of students had achieved a good level of understanding of classification indicators and giving examples, but only 50% were able to restate concepts completely. The supporting factors identified include learning motivation, parental mentoring, teacher learning strategies, and student absorption. On the other hand, barriers to understanding include lack of enthusiasm for learning, an unsupportive environment, and a lack of parental involvement. These findings confirm that the success of conceptual understanding is determined not only by cognitive aspects but also by comprehensive pedagogical and social support. This research makes an important contribution to the development of more contextual and participatory biology learning strategies, as well as opens opportunities for further research that explores the use of innovative media in strengthening conceptual understanding.